The European Statements of Hospital Pharmacy: achieving consensus using Delphi and World Café methodologies. Issue 5 (19th September 2014) - Maskrey, Neal; Underhill, Jonathan
Abstract : In developing the European Statements of Hospital Pharmacy, a method was required that afforded participants the opportunity to contribute to the wording of the statements, and provided a way to measure the level of agreement. Given the diversity of hospital pharmacy service delivery across Europe, it was envisaged that an explicit, objective and inclusive approach was required to achieve consensus. A two stage approach was therefore designed: a Delphi process followed by a World Café workshop. The sequential use of these two processes in a highly complex context with a requirement for significant international collaboration was highly successful as a consensus building approach. We recommend the sequential use of these two techniques for achieving consensus in similarly complex decision making processes.